2014
DOI: 10.1152/ajpgi.00178.2013
|View full text |Cite
|
Sign up to set email alerts
|

The role of receptor tyrosine kinase activation in cholangiocytes and pulmonary vascular endothelium in experimental hepatopulmonary syndrome

Abstract: Pulmonary vascular dilation and angiogenesis underlie experimental hepatopulmonary syndrome (HPS) induced by common bile duct ligation (CBDL) and may respond to receptor tyrosine kinase (RTK) inhibition. Vascular endothelial growth factor-A (VEGF-A) expression occurs in proliferating cholangiocytes and pulmonary intravascular monocytes after CBDL, the latter contributing to angiogenesis. CBDL cholangiocytes also produce endothelin-1 (ET-1), which triggers lung vascular endothelin B receptor-mediated endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
1
25
0
3
Order By: Relevance
“…We have also shown that overexpression of endogenous inhibitors of angiogenesis implicated in our human studies (angiostatin and endostatin) reduced lung microvessel counts and normalized alveolar‐arterial oxygen gradient (AaPO 2 ) in the experimental model, supporting the key role of lung neovascularization in HPS . Finally, we have shown that the multispecific tyrosine kinase inhibitor sorafenib reversed vascular proliferation in the lungs and improved gas exchange in the rodent model when administered after the establishment of HPS …”
supporting
confidence: 63%
See 1 more Smart Citation
“…We have also shown that overexpression of endogenous inhibitors of angiogenesis implicated in our human studies (angiostatin and endostatin) reduced lung microvessel counts and normalized alveolar‐arterial oxygen gradient (AaPO 2 ) in the experimental model, supporting the key role of lung neovascularization in HPS . Finally, we have shown that the multispecific tyrosine kinase inhibitor sorafenib reversed vascular proliferation in the lungs and improved gas exchange in the rodent model when administered after the establishment of HPS …”
supporting
confidence: 63%
“…Historical studies and pathologic specimens from patients demonstrate increased vascularity in the lung . Administration of sorafenib to rats after common bile duct ligation (which recapitulates HPS) reverses abnormal oxygenation, reduces intrapulmonary vascular dilations and shunting, and decreases circulating monocytes and progenitor cells …”
Section: Discussionmentioning
confidence: 99%
“…35,38,39 Inhibition of nitric oxide synthase, the endothelin-B receptor, and vascular endothelial growth factor has mitigated HPS in animal models. [40][41][42] Notably, these same mediators have also been implicated in POPH and endothelin receptor antagonists (dual and selective), and phosphodiesterase-5 inhibitors are mainstays of therapy for PAH and POPH. 14 Additionally, a substantial degree of overlap has been described in the histologic findings of each condition.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of sorafenib may be attributed to at least three mechanisms. First, sorafenib might indirectly mitigate HPS by improving underlying liver injury, fibrosis, and PH . Second, sorafenib directly targets the VEGF/VEGFR‐2/Akt pathway and pulmonary angiogenesis in the pulmonary microvasculature in vivo and in rat pulmonary microvascular endothelial cells in vitro .…”
Section: Pathogenesis Of Hps: Lessons From Experimental Modelsmentioning
confidence: 99%